EFFECTS OF THE SERVICE QUALITY TO CUSTOMER LOYALTY MEDIATED BY SATISFACTION VARIABLE - Marsudi Marsudi (Journal of International Conference Proceedings (JICP), 2019)
The purpose of this study was to analyze and assess the effect of service quality on customer loyalty mediated by satisfaction variables on depositors or customers of Bank BNI Malang. The sampling technique in this study using the purposive sampling of 100 respondents to the depositors or clients who use the services of BNI Malang are already quite mature and has been transacting at least twice. Data collection techniques used is by using a questionnaire. The analytical tool used in this study uses regression analysis to test mediation Sobel test. Sobel test results show that the probability value is less than the value of alpha, indicating that the quality of service is a positive and significant impact on customer loyalty mediated by satisfaction variables.